ANALYSIS OF INVENTORY CONTROL OF FLOUR AND REFINED SUGAR RAW MATERIALS BASED ON THE ECONOMIC ORDER QUANTITY (EOQ) METHOD CASE STUDY AT SNACK FOOD COMPANY - Safa'at, Safa'at; Zebua, Martin (JURNAL ILMIAH EDUNOMIKA, 2024)
In running large-scale production, raw materials are needed in large quantities. Careful planning is needed so that raw material inventory can be managed optimally and on target, so that it can meet production needs. Inventory control is very important to achieve this goal. Control is an important aspect of inventory management, which can help companies achieve the desired profit. In this study, researchers used a qualitative approach by analysing existing data in a snack food company. The results showed that the inventory analysis of raw materials for wheat flour and refined sugar in the company was not optimal. From the analysis of the EOQ method, it was found that the amount of flour raw material inventory was 11,912 kg with a purchase frequency of 30 times per year, while for refined sugar it was 10,212 kg with a purchase frequency of 59 times. In conclusion, there is a difference in total inventory costs for flour raw materials of Rp 38,670,189 and for refined sugar of Rp 122,117,065 compared to the company's current policy.